LATIHAN ABDOMINAL DRAWING-IN MANEUVER SAMA BAIKNYA DENGAN CORE STRENGTHENING EXERCISE DALAM MENINGKATKAN KEKUATAN OTOT PENYANGGA TUBUH PADA SISWI SMAN 1 GIANYAR - I Gusti Ayu Mega Purwani; Ni Wayan Tianing; I Putu Adiartha Griadhi (Majalah Ilmiah Fisioterapi Indonesia, 2017)
ABSTRACTThis study aims to determine the effect of abdominal drawing-in maneuver and core strengthening exercise inincreasing the strength of the core muscles performed on female students SMAN 1 Gianyar. The research designused Randomize Pre and Post Test with Control Group Design with sampling technique using simple randomsampling so that 30 samples were divided into 2 groups, the treatment group (abdominal drawing-in maneuver) andthe control group (core strengthening exercise) 3 times a week for 4 weeks. There was a significant increase of coremuscle strength in both groups with mean improvement in treatment group of 64,05 ± 23,6 (p <0,05) and controlgroup was 69,91 ± 23,2 (p <0,05) . Based on paired sample t-test in the treatment group and control group, there wasno significant result (p> 0,05) in both groups which means abdominal drawing-in maneuver practice as well as corestrengthening exercise in increasing the strength of the core muscle.Keyword : Core Muscle, muscle strength, Abdominal Drawing -in Maneuver, Core Strengthening Exercise